Zero-bias mid-infrared graphene photodetectors with bulk photoresponse and calibration-free polarization detection - Jingxuan Wei; Ying Li; Lin Wang; Wugang Liao; Bowei Dong; Cheng Xu; Chunxiang Zhu; Kah-Wee Ang; Cheng-Wei Qiu; Chengkuo Lee (Nature Communications, 2020)
Here, graphene-based plasmonic metamaterials are used to generate an artificial bulk photovoltaic effect, enabling the realization of mid-infrared photodetectors with enhanced responsivity and calibration-free polarization detection at room temperature.